SDH-deficient renal cell carcinoma: a clinicopathological analysis highlighting the role of genetic counselling - Wilczek, Y; Sachdeva, A; Turner, H; Veeratterapillay, R (Annals of the Royal College of Surgeons of England, 2021)
Succinate dehydrogenase (SDH)-deficient renal cell carcinoma (RCC) accounts for 0.05–2% of all RCCs. The majority of patients have germline mutations, most frequently in the SDHB gene. People with these mutations are predisposed to developing paragangliomas, phaeochromocytomas and gastrointestinal stromal tumours. Patients should be referred to genetic services for further workup and close surveillance imaging due to the risk of development of further tumours. We present a woman with SDH-deficient RCC and review the literature associated with this uncommon entity.